Representation of the Pancasila Learner Profile in Grade 12 EFL textbooks with Merdeka Curriculum - Alvandha Adindra; Misbahul Amri; Lestari Setyowati (Eduvest - Journal of Universal Studies, 2025)
This study investigates the extent to which visuals and visual texts in the Merdeka curriculum EFL textbooks for grade XII depict the characteristics of a good Pancasila student. The research employs a qualitative approach and content analysis to examine the official textbook "Bahasa Inggris Life Today" published by the Indonesian Ministry of Education and Culture in 2022. The analysis focuses on how the visuals represent the six dimensions of the Pancasila Student Profile, including faith, global diversity, mutual cooperation, independence, critical thinking, and creativity. Findings reveal that the textbook effectively illustrates these dimensions through various visual representations and assignments, promoting character development in accordance with the Pancasila values. However, some misrepresentations were identified, particularly regarding the depiction of the Baduy tribe, suggesting the need for further analysis in future studies. Ultimately, the textbook serves as a vital resource for implementing the Merdeka curriculum and fostering students' understanding of Pancasila value